STRATEGIES FOR DEVELOPING AND SUSTAINING MOTIVATION IN L2 ENGLISH ACQUISITION: A COMPREHENSIVE FRAMEWORK (SCIENCE TIME JOURNAL, 2026)
Motivation is widely recognized as a primary determinant of success in Second Language Acquisition (SLA). However, the transition from initial "initialization" to long-term "sustainment" remains a significant pedagogical challenge. This article proposes a comprehensive framework for developing and maintaining motivation in L2 English learners by synthesizing Self-Determination Theory (SDT) with the L2 Motivational Self System (L2MSS). Through a mixed-methods study of 1,200 adult learners, this research identifies the critical roles of autonomy, vision-building, and "micro-win" validation. Results indicate that learners who successfully internalize their "Ideal L2 Self" show a 40% higher persistence rate over 18 months compared to those driven by external pressures. The study concludes with actionable strategies for educators to foster a resilient motivational ecosystem.